THE OBSERVER OBSERVED - Nico J.G. Kaptein (IAIN Tulungagung, 2021)
In his seminal Islam Observed: Religious Developments in Morocco and Indonesia from 1968, the American anthropologist Clifford Geertz (1926-2006) placed the comparative study of Muslim societies on the research agenda. In view of my knowledge on the history of Islam in Indonesia, it stroke me that the political dimension of religion did not take an important place in the book. This is the more remarkable because during Geertz’s fieldwork in Java in 1953-4 manifestations of political Islam regularly popped up, and Geertz did not only notice those, but also recorded them in his book The Religion of Java from 1960. In this paper I will go into the question of why Geertz did not give a more prominent place to political Islam in his analysis of Muslim cultures, and what concepts of both Islam and religion he used.